Liveworksheet-Based E-LKPD and Interest in Learning Improves Science and Social Learning Outcomes for Elementary School Students - Tika Fahmi Afifah; Junaedi, Akhmad (Journal of Education Reseach and Evaluation, 2024)
This research was motivated by students who had difficulty understanding the learning material. This impacts low student learning outcomes due to using less creative and innovative learning media in grade IV elementary school. This study aims to analyze the influence of direct worksheet-based E-LKDP and interest in learning on social studies learning outcomes for fourth-grade elementary school students. This research design uses a quantitative type of research. The research method used in this research is the correlational research method. The population in this study was 132 students. The sampling technique used in this research is Probability Sampling with the Simple Random Sampling type. The methods used to collect data are interviews, questionnaires and documentation. The instruments used in this research are questionnaires and documentation. The techniques used to analyze data are descriptive statistical analysis, analysis prerequisite tests, and hypothesis testing. The research results show that the influence of live worksheet-based E-LKPD and interest in learning on the learning outcomes of class IV students in science subjects is significant. It was concluded that live worksheet-based E-LKPD can improve the learning outcomes of class IV students in science subjects.